Gender Quotas for Corporate Boards: Attitudes and Progression - Latham, Jillian Anne (Curtin University, 2022)
This constructivist-interpretivist research examined actors’ attitudes towards the prospect of legislated gender quotas for ASX200 boards in Australia. Thematic analysis demonstrated ongoing resistance towards board gender diversity, a preference for maintaining the status quo, and limited desire for structural change. A stark polarisation between actors who support and oppose board gender quotas was uncovered. These findings advance the board diversity literature and have implications for the progression of board gender composition in Australia.